A Case of Black Esophagus - Haddad, Ibrahim (Cureus, 2019)
Acute esophageal necrosis, commonly known as black esophagus, is a serious clinical condition that requires prompt diagnosis and management to improve morbidity and mortality. We present a 47-year-old woman who had this potentially lethal condition. The patient initially presented with hematemesis, and esophagogastroduodenoscopy at presentation showed diffuse esophageal ulcerations, erosions, and necrosis. During her admission, she required multiple blood transfusions for active bleeding, after which her clinical condition stabilized. Repeat esophagogastroduodenoscopy showed near-complete resolution of the earlier findings.